Estudantes campesinos de escolas multisseriadas da comunidade Ponta da Serra, Arraias/TO: para além dos estigmas - Silva, Elziene Araújo da (Universidade Federal do Tocantins, 2019)
The present work has the objective of discussing the peasant students of multiseriate schools in the punta da serra community: highlights in education in the region of Arraias-TO, which sought to demystify the stereotypes in relation to peasant students as well as to discuss the trajectory of these peasant students pointing (2006), Amorim (2005), Arroyo, Caldart and Molina (2008), among other important authors who discuss the theme in question. The methodology used was based on a qualitative approach, consisting of participant observation, taking into account that the researcher was also a peasant student and is currently an educator in this context. Five people who were former students and peasant educators participated in the study. The application of semi-structured interviews. Among the results we can highlight that the students from the field are as capable as those who live in the city, that the external factors that influence this are real, define the potential of each independent of being from the countryside or the city. However, some students take longer to develop, follow their time, and there are other children who learn more easily. For that, we can see what makes the difference is the support of the family and the teacher, together with the pedagogical support of the state and municipal education departments and that the student of the field